Specification of mechanisms of earthquake sources in the Carpathian region - D. V. Malitskiy; O. D. Gritsay; O. O. Muyla; O. I. Kutniv; E. M. Kozlovskiy (Геофизический журнал, 2014)
One of the urgent problems - a solution of the focal mechanism of an earthquake is considered. On the example of several events occurred in the Carpathian region of Ukraine, the solving of this problem with a graphic method is proposed. This method is based on identifying the best location option of nodal planes relatively to both the fuzzy P-wave arrivals and the values of the logarithm of the ratio of the S-wave amplitude to the P-wave amplitude. A sequence of plotting diagrams for determining the focal mechanism is presented. The focal mechanisms and types of faults are determined by using this method for 6 events occurred in the Transcarpathian region. The similarity of the focal mechanisms for repeated earthquakes is shown. The dynamic parameters of the sources of 4 earthquakes occurred in 2012-2013 are retrieved by using data from the spectra of records converted into displacements according to the Brune model.